2004
DOI: 10.1016/j.jacc.2004.05.008
|View full text |Cite
|
Sign up to set email alerts
|

Vascular Brachytherapy and Coronary Stenting for De Novo Lesions

Abstract: Although vascular brachytherapy (VBT) has proved to be effective and safe for the treatment of in-stent restenosis (1-8), its role in the treatment of de novo lesions remains unclear. The clinical trials that were designed to study the effectiveness of various beta radiations for the treatment of de novo coronary lesions reported mixed results. Although feasibility studies such as the Beta Energy Restenosis Trial (BERT) (9), which used 90Sr/Y, the Proliferation Reduction and Vascular Energy trial (10), which u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2006
2006
2006
2006

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 26 publications
0
1
0
Order By: Relevance
“…Stent restenosis therapy headed down its own road following pivotal brachytherapy trials that demonstrated benefit among patients with ISR but not with de novo lesions (12)(13)(14)(15). Treatment of de novo lesions focused on optimization of final lumen diameter with stents.…”
Section: See Page 2152mentioning
confidence: 99%
“…Stent restenosis therapy headed down its own road following pivotal brachytherapy trials that demonstrated benefit among patients with ISR but not with de novo lesions (12)(13)(14)(15). Treatment of de novo lesions focused on optimization of final lumen diameter with stents.…”
Section: See Page 2152mentioning
confidence: 99%